Analysis of the Impact of Strategic Leadership on Organisational Performance: A Study of Afe Babalola University, Ado-Ekiti - Olowoyeye, Ajoke Seun; Adegoke, Omofolasaye Omobolanle (African Journal of Stability and Development (AJSD), 2025)
This study examined the impact of strategic leadership on organisational performance, with a focus on strategic agility and strategic communication as key leadership dimensions. Afe Babalola University, Ado Ekiti (ABUAD) served as the case study institution, given its rapid institutional growth and reputation for strategic innovation. The study employed a quantitative, cross-sectional survey design, and data were collected from 192 academic and non-academic staff using a structured questionnaire. Descriptive statistics, Pearson correlation, and multiple regression analyses were used to analyse the data. Results showed that both strategic agility (β = 0.426, p < 0.001) and strategic communication (β = 0.403, p < 0.001) had significant positive effects on organisational performance. The combined model explained approximately 59.9% of the variance in performance outcomes. These findings underscore the importance of leadership behaviours that enhance adaptability, clarity of vision, and participatory communication in achieving institutional goals. This study is significant because it highlights the insufficiently studied yet pivotal role of specific strategic leadership practices in driving university performance. By isolating strategic agility and communication as key predictors, the study provides empirical evidence that can inform leadership development, governance reforms, and policy strategies in higher education. It concludes that strategic leadership is a critical driver of organisational success and recommends that universities invest in agility training, robust communication systems, and decentralised decision-making practices to strengthen institutional effectiveness.